Why Do We Pursue Ed.D.?: A Qualitative Analysis on the Motivation of Chinese Candidates - Gong, Wenting; Wang, Weihua; Xu, Chuang (Frontiers in Psychology, 2022)
This study aims to explore what motivates Chinese mid-career educational practitioners to pursue Ed.D. A university in South China was selected as a case university, and 18 Ed.D. candidates were recruited to participate in semi-structured interviews. Grounded theory analysis was conducted on the transcripts of the interviewees’ information. The findings uncovered four motivational patterns (pre-intrinsic,pre-extrinsic, post-intrinsic, and post-extrinsic) of Ed.D. candidates in China that mutually influence and reinforce one another. A theoretical model was thus constructed in which extrinsic factors moderate intrinsic factors, prepositional factors stimulate post-positional factors, with pre-intrinsic factors act as incentives, pre-extrinsic factors act as preconditions, post-intrinsic factors and post-extrinsic factors act as internal and external reinforcers, respectively. This study broadens critical understanding of Ed.D. students’ motivation and offers several implications that should be of interest to Chinese Ed.D. candidates, educational researchers, universities, and government officials.